Quality assessment and stability study of compounded furosemide syrup - Alfred-Ugbenbo, Deghinmotei; Zdoryk, Oleksandr; Georgiyants, Viktoria (ScienceRise: Pharmaceutical Science, 2017)
Compounded oral preparations, made with use of manufactured products as sources of active pharmaceutical ingredients, are characterized by short beyond-use-dates due to their instability. Aim: The aim of this study is to investigate the physical, chemical and microbiological stability of compounded furosemide syrups within a 30 days period. Methods: Batches of 5 mg/ml compounded syrups, using furosemide substance and commercial tablets (two brands) as sources of active pharmaceutical ingredients, were stored in the dark at 5±3 °C and 23±2 °C and examined at days 0, 7, 15, 23, and 30 for changes in physical (pH, formation of colour, gas, odour and changes in viscosity), chemical and microbial stability. A stress test was conducted in order to distinguish signs of chemical instability using a stability-indicating thin-layer chromatographic method. Bacterial inoculation of these samples were examined for microbial stability based on the total aerobic microbial count (TAMC <100), the total combined yeasts/moulds count (TYMC <10) and absence of Escherichia coli. Results: Throughout the storage period the investigated syrups showed no extra spots on the chromatogram, no significant changes in pH, colour, odour, gas formation, viscosity. On day 30, the content (≥99.3%) of furosemide, total aerobic microbial count (< 102), total combined yeasts/moulds count (<101) in studied samples were within acceptable limits. Stressed samples showed presence of extra and diminished spots. Conclusions: Extemporaneous syrups of furosemide substance and dispersed furosemide tablets, stored in glass bottles in the dark at 5±3 °C and 23±2 °C, was found to be physically, chemically and microbiologically stable for at least 30 days